The cities of the Iazygians - Fehér, Bence (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Ptolemy’ description of the Iazygian territory (Geogr. hyph. III 7) describes eight ‘poleis’ – which could be any kind of settlement indeed by name, and the boundaries of the region. The boundaries can be traced from the Greater Fatra range in the north to the river Temes or Krassó in the south, but the position of the settlements allows for some variations, taking as a fix point Partiskon = Szeged, from where a probable trade route started to the north or northwest, reaching most of the settlements mentioned. If the direction of the route in Ptolemy’s map were correct, some localities were outside of the actual territory (A), but supposing two different kinds of distortion, we may reconstruct a route heading to the Zagyva–Tarna region (B) or to Aquincum (C). Both possibilities seem realistic, but the most important settlement in the first part of the 1st c. was Bormanon (according to Geogr. hyph. VIII 11). The etymology of the name points to a warm or/and medicinal water spring. This fact and the date makes the B the most probable version.